2020
DOI: 10.1021/acsomega.0c05288
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Treatment Strategy of Aquatic Environments: Oxidative Degradation of Penicillin G by Chromium Trioxide in Acidic Media and the Impact of Metal Ion Catalysts: Kinetics and Mechanistic Insights

Abstract: Degradation kinetics and pathways of the antibiotic penicillin G (Pen) have been examined via oxidation by chromium trioxide (Cr VI ) in aqueous sulfuric and perchloric acid media. The oxidation reactions were monitored by spectrophotometry at 298 K. In both acidic media, penicillin G oxidation was set to proceed through acid catalysis. The stoichiometry of the reactions designated that 3 moles of Pen required 2 moles of Cr VI . The kinetics of Pen oxidation in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…NPs interact with cellular organelles and biomolecules such as DNA, enzymes, ribosomes, and lysosomes, influencing cell membrane permeability, protein activation, gene expression, and oxidative stress [48]. In the current study, PEG/TiO 2 (2) was effective against all tested bacterial strains, in close agreement with other previous works [86,87]. As PEG/TiO 2 NPS are smaller in size, they are expected to have a better chance of interacting with bacteria or better access to endogenous bacterial proteins.…”
Section: Antimicrobial Performance Evaluationmentioning
confidence: 80%
See 2 more Smart Citations
“…NPs interact with cellular organelles and biomolecules such as DNA, enzymes, ribosomes, and lysosomes, influencing cell membrane permeability, protein activation, gene expression, and oxidative stress [48]. In the current study, PEG/TiO 2 (2) was effective against all tested bacterial strains, in close agreement with other previous works [86,87]. As PEG/TiO 2 NPS are smaller in size, they are expected to have a better chance of interacting with bacteria or better access to endogenous bacterial proteins.…”
Section: Antimicrobial Performance Evaluationmentioning
confidence: 80%
“…The question is, what is the effect of adding a sulfa drug to the composition of compound (2)? The results indicated that this combination significantly modifies the properties of the sulfaguanidine and increases antibacterial and antibiotic efficacy when mixed with PEG/TiO 2 /Drug (5), compared to using the pure drug (SULFA) or even using a mixture of PEG/TiO 2 (2). Moreover, the efficacy was much higher in the use of PEG/α-CD/TiO 2 (3) polymer, but the effect only occurred on Gram-negative strains; even after the addition of a sulfaguanidine to the complex, i.e., PEG/α-CD/TiO 2 NPs/Drug (6), the efficacy was also only good against Gram-negative strains.…”
Section: Antimicrobial Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In various media, medical drugs are generally subjected to a variety of oxidation processes resulting in their decomposition or degradation. Throughout these oxidation processes, oxidizers convert harmful or toxic materials to lower toxic ones which can be discharged safely to the environment. Thus, oxidation of medical drugs has been considered as one of the supreme substantial methods for drug degradation and water-treating processes . Fluconazole is a significant antifungal drug utilized for a wide number of fungal infections.…”
Section: Introductionmentioning
confidence: 99%
“… 26 30 Thus, oxidation of medical drugs has been considered as one of the supreme substantial methods for drug degradation and water-treating processes. 31 Fluconazole is a significant antifungal drug utilized for a wide number of fungal infections. Literature review illuminated very few reports that have been published on the oxidative degradation of fluconazole.…”
Section: Introductionmentioning
confidence: 99%